If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(2y + 1) + 2y = 14 Reorder the terms: 2(1 + 2y) + 2y = 14 (1 * 2 + 2y * 2) + 2y = 14 (2 + 4y) + 2y = 14 Combine like terms: 4y + 2y = 6y 2 + 6y = 14 Solving 2 + 6y = 14 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 6y = 14 + -2 Combine like terms: 2 + -2 = 0 0 + 6y = 14 + -2 6y = 14 + -2 Combine like terms: 14 + -2 = 12 6y = 12 Divide each side by '6'. y = 2 Simplifying y = 2
| (x^5+x^3+x)(x^2-1)= | | 23.08-22.1= | | 25+6(x-3)=37 | | 103.2-98.6= | | -5t+6+6t=9 | | 5x-21=-y | | 157-6x=4x+17 | | 81y^4-18y^2+1= | | 3(2x-4)=36 | | 11=-p | | 6x+14=-98-8-8x | | (5x^2-4x-1)(7x^2+9x+8)= | | 13-8x=43-29x | | 50-7x=2x+21 | | 4(9d+2v)+3(7v-d)= | | 7-10x=39-17x | | 4x-10=-14-2x | | (x^2+x+8)(x-5)= | | 12x+5=x+16 | | 3=s-10 | | x^2-3x-304=0 | | X^3-15X+56=0 | | -77-10x=39-17x | | 5x^2-70x+75=0 | | -20=-4x | | -2x-5x=-56 | | p-5=-14 | | (6x^2-2x-6)(8x^2+7x+8)= | | 6x-4=16x-84 | | 4y=-20 | | 4x+3x=112 | | 1-6x=7-8x |